Tunable narrowband THz generation in orientation patterned gallium phosphide for THz anisotropy identification - McNee, I.; Tekavec, P.; Kozlov, V.; Markelz, A. G.; George, D. K.; Schunemann, P. (Nonlinear Frequency Generation and Conversion: Materials and Devices Xviii, 2019)
We demonstrate tunable narrowband THz generation by optical rectification of a femtosecond pulse in Orientation Patterned Gallium Phosphide. Center frequencies of 0.9 - 3.8 THz with average power up to 15 mu W were achieved using a 1.064 mu m fiber laser for the pump laser. Biomolecular characterization for an early application of this system is also shown in this work by anisotropic spectroscopic signature detection of molecular crystals in the THz region.
ISI Document Delivery No.: BM9XB Times Cited: 2 Cited Reference Count: 8 Cited References: Fejer M. M., 2013, ANTIPHASE DOMAIN ANN, P258 Jepsen PU, 2011, LASER PHOTONICS REV, V5, P124, DOI 10.1002/lpor.201000011 Lee YS, 2000, APPL PHYS LETT, V76, P2505, DOI 10.1063/1.126390 Niessen K. A., BIOPHYSICAL J, V112, P933 PARSONS DF, 1971, APPL OPTICS, V10, P1683 Singh R., 2013, MODULATED ORIENTATIO Tassev V., 2013, SPIE LASE, P9 Tekavec P., 2017, FRONTIERS OPTICS 201 McNee, Ian Tekavec, Patrick Kozlov, Vladimir Markelz, A. G. George, D. K. Schunemann, Peter Proceedings Paper Conference on Nonlinear Frequency Generation and Conversion - Materials and Devices XVIII Feb 05-07, 2019 San Francisco, CA Spie 1000 20th st, po box 10, bellingham, wa 98227-0010 usa 0277-786x Unsp 1090218
Keywords: anisotropy; biomolecules; femtosecond; optical rectification; orientation patterned gallium phosphide; Terahertz; THz generation